Determination of bisphenol A in commercial cat food marketed in the Czech Republic - Maršálek, Petr; Kovaříková, Simona; Lueerssen, Friedrich; Večerek, Vladimír (Journal of feline medicine and surgery, 2022)
OBJECTIVES: Bisphenol A (BPA) is one of the most widely used synthetic compounds on the planet. It is used in the synthesis of polycarbonate plastics, epoxy resins and other polymer materials. Owing to its excellent chemical and physical properties, it is used to produce food and beverage containers or the linings for metal products. BPA has been mentioned as a possible cause of feline hyperthyroidism. Cat food is considered one of the main sources of BPA intake. The purpose of this study was to evaluate BPA concentration in various types of commercial cat food available in the Czech Republic. METHODS: In total, 172 samples prepared from 86 different types of commercial cat food were assessed. The concentration of BPA was measured using liquid chromatography-tandem mass spectrometry. RESULTS: Measurable concentration of BPA was found in all samples (range 0.065-131 ng/g), with the highest concentration (mean ± SD) of BPA in canned food (24.6 ± 34.8 ng/g). When comparing BPA concentration in food trays (1.58 ± 0.974 ng/g), pouches (0.591 ± 0.592 ng/g) and dry food (1.18 ± 0.518 ng/g), concentrations of BPA in food trays and dry food were significantly higher (P <0.01) compared with pouches. Comparing BPA concentrations in canned food of different manufacturers, statistically significant differences were found as well. CONCLUSIONS AND RELEVANCE: The highest concentrations of BPA were found in cans. Thus, cans represent the highest possibility of exposure to BPA in comparison with other types of commercial feline food.
Keywords: fenoly; krmivo pro zvířata; Animal Feed; Animals; Česká republika; Phenols; Hyperthyroidism; Cats; kontaminace potravin; zvířata; Benzhydryl Compounds; pouch; Czech Republic; food tray; kočky; canned food; Food Contamination; benzhydrylové sloučeniny